Pemodelan Perbaikan Tanah dengan Injection Pile berbasis Metode Elemen Hingga (Plaxis 2D) pada Taxiway Bandara Soekarno-Hatta - editor1 (Fakultas Teknik dan Rekayasa, 2022)
This research is a modeling based on the finite element method using BorLog (N-SPT) data on the airport taxiway and analyzes parameters or soil correlation. The purpose of this modeling is to analyze the modeling of the pile on a medium soft soil profile that has been improved soil (soil improvement) with Injection Pile based on the required settlement criteria during the construction period of <100 mm / year. So from the results of the analysis, soil improvement on the taxiway shows a land subsidence of 0.01657 m at the group pile (100 m overall) and 0.02375 m at the cluster pile (part 40 m). The reduction of the taxiway using the Injection Pile method can be applied as a soil improvement to increase the carrying capacity and reduce excessive settlement during the construction period.